Two regularity criteria of the 3D magneto-micropolar equations in Vishik spaces - Bo Xu; Jiang Zhou (Electronic Journal of Qualitative Theory of Differential Equations)
In this paper, we utilize the Littlewood–Paley decomposition theory to establish two regularity criteria for the 3D magneto-micropolar equations in Vishik spaces, specifically focusing on the gradient of the velocity field.